Gamifikasi dan Media Interaktif Digital Dalam Meningkatkan Motivasi Belajar Siswa PAI - Ana Rahma Wati; Sofia Karema; Indiana Puspita Dewi; M. Rifky Shahada Pratama; Abdul Aziz (MJI Publisher by PT Mitra Jurnal Indonesia, 2026)
Abstract This study aims to analyze the role and utilization of gamification and digital interactive media in enhancing the learning motivation of Islamic Religious Education students. The rapid advancement of digital technology demands continuous innovation within the instructional process to make it more engaging, effective, less monotonous, and highly relevant to the unique characteristics of the current generation. Gamification serves as a learning approach that seamlessly integrates game elements such as points, levels, challenges, and rewards into educational activities, thereby significantly boosting student engagement and active participation. Concurrently, digital interactive media, including instructional videos, podcast applications, Augmented Reality (AR), Virtual Reality (VR), and game-based learning platforms, provide a more varied, flexible, and easily accessible learning experience at any given time. This study employs a qualitative approach utilizing the literature review method. Data were gathered from various reputable scientific sources relevant to the implementation of gamification and digital media in PAI learning. The results indicate that the integrated application of gamification and digital interactive media effectively increases students' learning motivation. Students become more enthusiastic, responsive, and active during lessons. Furthermore, the learning atmosphere becomes more enjoyable and dynamic, positively impacting their understanding of religious concepts. However, this study also identifies a negative impact: a potential reduction in students' focus on core material if game elements become overly dominant. Consequently, PAI teachers are expected to optimize technological utilization wisely, designing innovative, balanced, and adaptive learning environments to achieve maximum educational outcomes. Abstrak Penelitian ini bertujuan untuk menganalisis peran serta pemanfaatan gamifikasi dan media interaktif digital dalam meningkatkan motivasi belajar siswa Pendidikan Agama Islam (PAI). Perkembangan teknologi digital yang pesat menuntut adanya inovasi dalam proses pembelajaran agar lebih menarik, efektif, tidak monoton, dan relevan dengan karakteristik generasi saat ini. Gamifikasi merupakan pendekatan pembelajaran yang mengintegrasikan elemen permainan seperti poin, level, tantangan, dan penghargaan ke dalam kegiatan belajar, sehingga mampu meningkatkan keterlibatan dan partisipasi aktif siswa. Di sisi lain, media interaktif digital seperti video pembelajaran, aplikasi podcast, Augmented Reality (AR), Virtual Reality (VR), dan game base learning memberikan pengalaman belajar yang lebih variatif, fleksibel, dan mudah diakses kapan saja. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi pustaka. Data diperoleh dari berbagai sumber ilmiah yang relevan terhadap implementasi gamifikasi dan media interaktif digital dalam pembelajaran PAI. Hasil penelitian menunjukkan bahwa penerapan gamifikasi dan media interaktif digital secara terpadu mampu meningkatkan motivasi belajar siswa, baik siswa menjadi lebih antusias, fokus, dan aktif dalam mengikuti proses pembelajaran. Selain itu, suasana belajar menjadi lebih menyenangkan dan tidak monoton, sehingga berdampak positif terhadap pemahaman materi. Namun juga terdapat beberapa dampak negatif yaitu berkurangnya fokus pemahaman pada materi. Dengan demikian, gamifikasi dan media interaktif digital dalam pembelajaran PAI menjadi strategi yang efektif untuk meningkatkan motivasi belajar siswa. Oleh karena itu, guru diharapkan dapat memanfaatkan teknologi secara optimal serta merancang pembelajaran yang inovatif dan adaptif terhadap perkeihumbangan zaman guna mencapai hasil pembelajaran yang maksimal.